A High Catalytic Activity Photocatalysts Based on Porous Metal Sulfides/TiO2 Heterostructures. Issue 1 (3rd December 2020) - Qian, Yongteng; Wang, Le; Du, Jimin; Yang, Hao; Li, Mancong; Wang, Yina; Kang, Dae Joon
Abstract: Porous metal sulfides/TiO2 (P‐MST) photocatalysts are successfully prepared via a low‐cost strategy. It is found that the P‐MST possesses a high crystallinity with average pore size of ≈500 nm, which greatly enhances the structural stability as well as catalytic activity. The catalytic properties of the P‐MST are examined by monitoring the degradation of rhodamine B (RhB) under visible‐light irradiation. Particularly, the optimized 7% Bi2 S3 –CdS–MoS2 –TiO2 heterostructures exhibit a remarkable catalytic performance (i.e., the degradation of RhB of ≈98.9%) and long‐term cyclic stability (i.e., the catalytic activity of ≈91.7% even after 30 cyclic test), compared with that of other P‐MST heterostructures. The exceptional catalytic performance may be ascribed to the following benefits: i) the porous structure supplies ample carrier charge transfer channels and lots of surface reaction sites; and ii) the suitable amount of metal sulfides grown on TiO2 have contributed to significant improvement of the electrical conductivity and the light absorption capability. Abstract : The porous metal sulfides/TiO2 heterostructures are successfully fabricated through a simple route. The porous metal sulfides/TiO2 heterostructures present an exceptional catalytic performance for the degradation of RhB under visible light irradiation, which is due to the porous structures can supply rich carrier charge transfer channels and abundant surface‐active sites during the photocatalytic process.